Energy scheduling model to optimize transition routes towards 100% renewable urban districts - Leeuwen, Richard van; Wit, Jan B. de; Smit, Gerard J.M. (International Journal of Sustainable Energy Planning and Management, 2017)
The purpose of this paper is to develop a model to analyze options for 100% renewable urban districts which self-consume locally generated renewable energy as much as possible and import (or export) energy from (or to) external grids as little as possible. Energy scheduling algorithms are developed to prioritize energy generation and storage of local renewable energy. The model is applied in a Dutch case study in which three renewable energy system concepts are evaluated against the case reference. Optimal capacities are determined for minimal operational costs including a penalty on carbon dioxide production. Attractiveness of these concepts is discussed in relation to costs, environmental concerns and applicability within the Dutch context of the energy transition.